Nutritive evaluation of Carcass Meal for growth and Carcass Characteristics in large White Yorkshire Pigs - Mary Sinthya V (Department of Animal Nutrition, College of Veterinary and Animal Sciences, 1998)
An investigation was carried out to assess the effect of carcass meal, a product processed from slaughter house by-products, on the growth rate, feed conversion efficiency, carcass quality and economics of production in growing and finishing pigs. The conventional animal protein supplement fish meal was replaced with carcass meal. Twenty four Large White Yorkshire female piglets with an average live weight of 20 kg were divided into four groups (Groups I, 11, III and IV) of six animals each as uniformly as possible. They were maintained on four isoproteimic and isocaloric diets T1, T., T) and T. containing 0, 6, 12 and 18 per cent in grower rations and at 0, 4, 8 and 12 per cent in finisher rations respectively of carcass meal replacing fish meal. The animals under all the four dietary treatments had similar growth rates with an overall average daily gain of 381, 389, 382 and 376 g for the groups I, II, III and IV respectively. The total feed intake of the animals in different groups were similar. There was no significant difference in the feed conversion efficiency among groups, the overall average values being 4.36, 4.56, 4.35 and 4.48 for the groups I, II, III and IV respectively.